Directly labeled mRNA produces highly precise and unbiased differential gene expression data - Gupta, Vineet (Oxford University Press, 2003)
Microarray based gene expression studies allow simultaneous analysis of relative amounts of messenger RNA (mRNA) for thousands of genes using fluorescently labeled nucleic acid targets. Most common methods use enzymatic techniques, such as oligo-dT primed reverse transcription to produce labeled cDNA. These labeling methods have a number of shortcomings, including enzyme- introduced labeling and sequence bias, laborious protocols, high experiment-to-experiment variability and an inability to detect small changes in expression levels. Here, we describe a novel labeling methodology that uses platinum-linked cyanine dyes to directly chemically label mRNA from as little as 2 µg of total RNA. We show that the gene expression data produced using the labeled mRNA method has very high precision, low error, no labeling bias and a dynamic range over several orders of magnitude. This allows a greater accuracy in the identification of differentially expressed genes and cuts down on the need for running too many replicate assays. Small changes in gene expression can now be detected in large-scale gene expression profiling assays using this simple, easy and quick procedure.